The metaphors of personification in «Qalachuyma, traditional aymara songs» - Mamani Mamani, Alan Ever (2018)
This paper is confined to the current of cognitive linguistics, which aims to categorize and analyze the metaphors of personification in traditional Aymara songs. The data have been collected in the songbook “Qala chuyma, traditional Aymara songs”. In analyzing the metaphors, three types of categorizations have been found: animals as animate beings,objects as animate beings, and customs as animate beings. It is concluded that the different metaphors expressed in the Andean elements show and acquire human qualities and attitudes. They coexist with the Aymara man in his daily work. Therefore, they are considered in the Andean world as animate beings.